Stereological analysis of sciatic nerve in chickens following neonatal pinealectomy: an experimental study - Turgut, Mehmet; Kaplan, Süleyman; Ünal, Burçin Zeynep; Bozkurt, Mehmet; Yürüker, Sinan; Yenisey, Çigdem; Sahin, Bünyamin; Uyanıkgil, Yigit; Baka, Meral (Journal of Brachial Plexus and Peripheral Nerve Injury, 2010)
Background Although the injury to the peripheral nervous system is a common clinical problem, understanding of the role of melatonin in nerve degeneration and regeneration is incomplete.Methods The current study investigated the effects of neonatal pinealectomy on the sciatic nerve microarchitecture in the chicken. The chickens were divided into two equal groups: unpinealectomized controls and pinealectomized chickens. At the end of the study, biochemical examination of 10 sciatic nerve samples from both groups was performed and a quantitative stereological evaluation of 10 animals in each group was performed. The results were compared using Mann-Whitney test.Results In this study, the results of axon number and thickness of the myelin sheath of a nerve fiber in newly hatched pinealectomy group were higher than those in control group. Similarly, surgical pinealectomy group had significantly larger axonal cross-sectional area than the control group (p < 0.05). In addition, the average hydroxyproline content of the nerve tissue in neonatal pinealectomy group was higher than those found in control group. Our results suggest that melatonin may play a role on the morphologic features of the peripheral nerve tissue and that melatonin deficiency might be a pathophysiological mechanism in some degenerative diseases of peripheral nerves. The changes demonstrated by quantitative morphometric methods and biochemical analysis has been interpreted as a reflection of the effects of melatonin upon nerve tissue.Conclusion In the light of these results from present animal study, changes in sciatic nerve morphometry may be indicative of neuroprotective feature of melatonin, but this suggestion need to be validated in the human setting.